Plant breeding for international markets and international branding partnership - Bugallo, Veronica Lucia (INTA, 2024)
The objetives of INTA are to facilitate the use of resources, promote associations, and promote scientific activities. INTA is located in the five regions of Argentina (Northwest, Northeast, Cuyo, Pampeana and Patagonia), through a centers, experimental stations, research institutes and extension units.